The Relationship between Husband's Support and the Anxiety Level of Pre-Sectio Caesarea Pregnant Women at X Hospital Denpasar - Ni Komang Wardani; Ni Made Risna Sumawati; Made Egar Adhiestiani (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2024)
World Health Organization states that the number of deliveries using cesarean section continues to increase globally. Women with pre-sectio caesarea surgery will experience anxiety. One of the things that can affect a pre-caesarean woman's anxiety level is her husband's support. The purpose of this study is to ascertain the association between pregnant women's anxiety levels before to cesarean section surgery and their husbands' support. Correlational analytical research using a cross-sectional design is this kind of study. Forty expectant women scheduled for cesarean sections in the X Hospital Denpasar delivery room comprised the study's sample. Chi-Square analysis was performed on the data. Of the 40 research respondents, 22 pregnant women (55.0%) received good support from their husbands in facing cesarean section surgery and 18 pregnant women (45.0%) received less support from their husbands. Twelve pregnant women (30.0%) reported having mild anxiety, sixteen (40.0%) reported having moderate anxiety, and twelve (30.0%) reported having severe anxiety. Pregnant women's anxiety levels prior to cesarean section surgery are correlated with their husbands' support, according to the Chi-Square test results (p-value = 0.044).For this reason, every husband should provide support to reduce his wife's anxiety level before a cesarean section.